What explains global inflation - Jongrim Ha; M. Ayhan Kose; Franziska Ohnsorge; Hakan Yilmazkuday (Koç University-TÜSIAD Economic Research Forum (ERF), 2023)
This paper examines the drivers of fluctuations in global inflation, defined as a common factor across monthly headline consumer price index (CPI) inflation in G7 countries, over the past half-century. We estimate a Factor-Augmented Vector Autoregression model where a wide range of shocks, including global demand, supply, oil price, and interest rate shocks, are identified through narrative sign restrictions motivated by the predictions of a simple dynamic general equilibrium model. We report three main results. First, oil price shocks followed by global demand shocks explained the lion's share of variation in global inflation. Second, the contribution of global demand and oil price shocks increased over time, from 56 percent during 1970-1985 to 65 percent during 2001-2022, whereas the importance of global supply shocks declined. Since the pandemic, global demand and oil price shocks have accounted for most of the variation in global inflation. Finally, oil price shocks played a much smaller role in global core CPI inflation variation, for which global supply shocks were the main source of variation. These results are robust to various sensitivity exercises, including alternative definitions of global variables, different samples of countries, and additional narrative restrictions.
Keywords: E31; E32; Q43; 330; Oil prices; demand shocks; supply shocks; interest rate shocks